BERFIKIR KRITIS DALAM PEMBELAJARAN MATEMATIKA - Adinda, Anita (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2016)
Critical thingking is thr ability to examine or analyze a source, to identify therelevant and irrelevant source, to identify and evaluate the assumtions, to implement strategies, to make decisions according to the assessment standarts. Critical thingking in mathematics is very important, because in everyday life the way a person directs his life depending on his/her believe statement, statement of receipt. Critical thingking makes people to analyze their own thingking to ensure that he has the choice and draw intelligent conclusion. Meanwhile, people who do not think critically, he can not dicide for himself what to think, what to believe and how to act. Having failed to think independently, he would imitate others, adopted the beliefs and accept the conclusions of others in passive. fordesigning mathematical problem that are expected to improve critical thingking skills, mathematical teacher must understand correctly what is desired and about which indicators will be developed. One problem may contain several indicators to be developed, but it must be considered the ability of students. It is no less important to note that critical thingking is as one of the high-level thingking skill so that not all students can achieve this level well. The role of a teacher and guidance is needed, so it can give help to every student.